Gestión curricular y logros de aprendizaje en las instituciones educativas pluridocentes de la parroquia Isinliví del cantón Sigchos en el año 2015. - Tuitice Quishpe, Alfredo (2016)
The researching tries to find the reality of curriculum management and learning achievement that is implemented in Educational Institutions Pluridocentes to Sigchos Canton, Insinliví Parish, because the main problem that these educative institutions is the lack of organization and inadequate arrangement in the curriculum, which is considered an essential part of education in the progress of new tools for the development of the most important aspects of student learning. The main objective proposed to solve this problem is the development of a proposal for the improvement of curriculum management, this proposal is a plan to improve curriculum management connected to learning achievements, whose purpose is to offer actions, goals and commitments that you must course the educational community in each school year, also help to safeguard achievements, solve priority problems and transform the educational management actions consistent and organized gradually and progressively, starting with the competing needs and giving managers a guide for routing and improve their actions successful, continuous and shared way simultaneous and complex task of being director and teacher in a simultaneous way, thus improving learning achievement, institutional and pedagogical practices in each school.